Middle managers in mergers and acquisitions: Agents and recipients of change - Teerikangas Satu (Edward Elgar Publishing, 2025)
In this chapter, I explore middle managers as agents and recipients of change, when they face radical organizational change. My focus is on one of the most enduring and impactful radical changes shaping organizations:  mergers and acquisitions (M&A). The aim of the chapter is to capture the characteristics of middle managers, who faced amidst radical organizational change, as in cross-border M&A, not only have to personally thrive amidst this change, but moreover, to act as the driving force of this change. The middle managerial challenge is embedded in this double-hatting - simultaneously delivering, whilst personally living through the same change. This leads me to argue that a middle manager’s development toward global leadership that makes a difference depends on one’s ability to personally undergo and lead such changes, when and where they arise. This requires learning to both implement change and personally make sense of change. Going forward, the chapter calls for academic, pedagogic and practitioner interest in (1) change as an inherent feature of today’s workplace, (2) the role of middle managers in organizations, and (3) the ‘inner world of change’, i.e. the personal experience of making sense of change and remaining resilient amidst change.
Research Handbook of Global Leadership: Making a Difference